I really need the answers to these binomial products.... (x+1)2-(x+1)(x-1)+(x-1)2= (2a+3)(a-1)+(a-1)2-(a-1)(a+1)= (m2-8)(m+2)-(m2+8m+2)(m-3)= Thanks
Follow Math Help Forum on Facebook and Google+
btw all the 2's after the numbers are all ment to representing to the power of 2 thingiy
expand the brackets ================================== factor out ========================== again expand the brackets and combine like terms you should get
Last edited by bigwave; Mar 9th 2010 at 05:05 PM. Reason: more info
View Tag Cloud